2022
DOI: 10.1002/ejhf.2514
|View full text |Cite
|
Sign up to set email alerts
|

Combination of late gadolinium enhancement and genotype improves prediction of prognosis in non‐ischaemic dilated cardiomyopathy

Abstract: Genotype and left ventricular scar on cardiac magnetic resonance (CMR) are increasingly recognized as risk markers for adverse outcomes in non-ischaemic dilated cardiomyopathy (DCM). We investigated the combined influence of genotype and late gadolinium enhancement (LGE) in assessing prognosis in a large cohort of patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…In regard to addressing the aforementioned dispute, Mirelis et al conducted a cohort study in which they demonstrated that the combination of late gadolinium enhancement from cardiac magnetic resonance (CMR) and positive genotype was useful in predicting SCD risk in patients with NICM and thus capable of stratifying the most qualified patients who benefit the most from primary prevention ICD therapy in this population. However, because CMR and genetic laboratories are time-consuming and hardly available in most healthcare institutions, as well as the restricted usage of gadolinium contrast in patients with end-stage renal disease, NT-pro BNP is still preferable to be used 17 35. Thus, more cohort studies evaluating the predictive efficacy of NT-pro BNP in ICM and NICM are highly needed to better understand the role of NT-pro BNP in stratifying patients with HFrEF who would benefit the most from ICD implantation for primary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to addressing the aforementioned dispute, Mirelis et al conducted a cohort study in which they demonstrated that the combination of late gadolinium enhancement from cardiac magnetic resonance (CMR) and positive genotype was useful in predicting SCD risk in patients with NICM and thus capable of stratifying the most qualified patients who benefit the most from primary prevention ICD therapy in this population. However, because CMR and genetic laboratories are time-consuming and hardly available in most healthcare institutions, as well as the restricted usage of gadolinium contrast in patients with end-stage renal disease, NT-pro BNP is still preferable to be used 17 35. Thus, more cohort studies evaluating the predictive efficacy of NT-pro BNP in ICM and NICM are highly needed to better understand the role of NT-pro BNP in stratifying patients with HFrEF who would benefit the most from ICD implantation for primary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals without a high-risk genotype and an LVEF ≥ 35%, the use of LGE on CMR imaging becomes an essential tool for risk assessment [127]. It is recommended that genetic testing, encompassing at least the PLN, LMNA, FLNC, and RBM20 genes, be conducted for patients with DCM and atrioventricular (AV) conduction delay before the age of 50, or if a family history of SCD in a first-degree relative is present [122].…”
Section: Arrhythmic Risk Stratificationmentioning
confidence: 99%
“…In this issue of the Journal, Mirelis et al 4 report data from a large retrospective study incorporating rare variant genetics with late gadolinium enhancement (LGE) CMR for the prediction of end-stage heart failure and malignant ventricular arrhythmia in patients with DCM. The curation of 600 DCM cases with previous CMR and genetic testing from several centres in Spain is to be commended.…”
Section: This Article Refers To 'Combination Of Late Gadolinium Enhan...mentioning
confidence: 99%